Genotype x environment interactions and stability analysis in elite lines of garlic (Allium safivum L.) - Lawande, A Khar, A Asha Devi, V Mahajan, K E (Journal of Spices and Aromatic Crops, 2005)
Thirty five elite lines and three released varieties of garlic (Allium sativum) were evaluated for their stability, with respect to yield and its contributing traits, for three years at Rajgurunagar (Maharashtra) during rabi season. Analysis of variance for stability of different characters indicated that mean differences for varieties and environments (years) were significant for all the characters except for number of leaves, indicating that the performance with respect to number of leaves in different years was not stable. Genotype 50 gave stable performance for higher plant height, clove weight, total yield and marketable yield, while genotypes 74 and 163 gave better yield under adverse situations. Genotype 117 had stability for dwarf plant height, less number of leaves and more equatorial diameter. Genotype 58 had stability in desired direction for less number of leaves and lesser neck thickness. Genotype 52 showed stability for higher plant height, greater neck thickness and average number of cloves with less number of leaves. Variety G-41 was stable for marketable yield only. In genotypes 52, 58, 117, 163,200, 229 and variety G-41, the yield was more in favourable environmental conditions.